Zero-link polymerized hemoglobin (OxyVita®Hb) stabilizes the heme environment: potential for lowering vascular oxidative stress. (19th May 2017) - Wollocko, Hanna; Anvery, Sarah; Wollocko, Jacek; Harrington, John M.; Harrington, John P.
Abstract: A study was conducted to compare the resistance to heme exposure between myoglobin, bovine hemoglobin, and OxyVita ® Hb (zero-link-hemoglobin-polymer). The rate of release of heme-iron is related to the tissue oxidative stress that can elicit deleterious effects in clinical uses of blood substitutes. Experimental work has focused on the unfolding of hemoglobin molecules, resulting in heme loss, by using urea as a denaturant and analyzing the Soret spectral region. These unfolding studies provide evidence for both the structural integrity and redox stability of OxyVita ® Hb and demonstrate that OxyVita ® Hb does not readily unfold and its heme exposure/release is greatly reduced.